Impaired Initiation But Not Execution of Contralesional Saccades in Hemispatial Neglect - Marlene Behrmann; Thea Ghiselli-Crippa; Ilaria Dimatteo (Behavioural Neurology)
Patients with unilateral neglect are impaired at making saccades to contralesional targets. Whether this problem arises from a deficit in perception, in planning the saccade or in executing the eye movement or some combination thereof remains unclear. We measured several variables related to the initiation and execution of saccades in an experiment which crossed two factors: target side (left, right) and direction of saccade (leftwards, rightwards). Relative to control subjects, patients with left-sided neglect were impaired in planning but not executing the contralesional saccade; while the latency to move their eyes following the onset of the target was increased, the duration and velocity to reach the target were normal. In addition, there were also no directional differences for saccades that were hypometric or inaccurate in the patients, further ruling out an execution impairment. Interestingly, this directional initiation deficit was exaggerated for leftward saccades to left targets, compared with all other conditions. We suggest that the disadvantage for contralesional saccades in neglect patients is attributable to a deficit not only in perceiving contralateral targets but also in planning leftward saccades. Once the saccade is initiated, however, execution apparently proceeds unimpaired.